Relativistic neoclassical fluxes in hot plasmas - Marushchenko, I.N.; Azarenkov, N.A.; Marushchenko, N.B. (Вопросы атомной науки и техники, 2013)
The radial fluxes of particles and energy with relativistic effects taken into account are represented in a form standard for neoclassical theory. All the formulations are based on the relativistic equations of motion and the relativistic drift-kinetic equation. As an illustration of the influence of relativistic effects, the radial neoclassical fluxes of electrons in 1/ν collisional regime are calculated and compared with those in the classical approach. The proposed formulation allows one to implement the relativistic effects in current transport codes. Радиальные потоки частиц и энергии, включающие релятивистские эффекты, представлены в форме, стандартной для неоклассической теории. Все формулировки основаны на релятивистских уравнениях движения и релятивистском дрейфово-кинетическом уравнении. В качестве иллюстрации влияния релятивистских эффектов на процессы переноса в плазме предлагается сравнительная оценка релятивистских и нерелятивистских радиальных неоклассических потоков электронов, посчитанных для стеллараторного режима 1/ν. Предложенная формулировка позволяет включить релятивистские эффекты в существующие транспортные коды. Радіальні потоки частинок та енергії, що ураховують релятивістські ефекти, запропоновано у формі, яка є стандартною для неокласичної теорії. Усі формулювання базуються на релятивістських рівняннях руху та релятивістському дрейфово-кінетичному рівнянні. В якості ілюстрації впливу релятивістських ефектів на процеси переносу в плазмі запропоновано порівняння релятивістських та нерелятивістських радіальних неокласичних потоків електронів, разрахованих для стелараторного режиму 1/ν. Запропоноване формулювання дозволяє ураховувати релятивістські ефекти в існуючих транспортних кодах.